An Introduction to a Revolutionary Low Density Bulk Explosive for Surface Blasting Operations - Hunsaker R. D (The Australasian Institute of Mining and Metallurgy, 1995)
The description, characteristics, advantages and application of a new bulk explosive for medium to large diameter dry blasthole conditions is described. A brief outline of the delivery system for the product is also included. This explosive has been designed to provide an alternative to ANFO, currently the most common bulk dry hole product available to the mining and quarrying industry. The selection of the optimum explosive for any blasting operation is of prime importance. It is a major factor contributing to the production of the desired results in terms of muckpile fragmentation, shape and diggability. The optimum explosive can be defined as the most cost-effective in producing satisfactory breakage and displacement of the material. ANFO satisfies this prerequisite for a significant proportion of dry hole applications. This unique, low density and low velocity of detonation explosive has been developed to provide the industry with a cost competitive alternative to ANFO. Typical loading or average inhole densities nominally range between 0.40 g/cc to 0.70 g/cc, depending on the application. Characteristics of this explosive allow for specific and common applications in open cut coal and metalliferous operations. These include ore/waste control operations, prestripping and presplitting applications, sites confronting cap rock problems, and large hole diameter quarries.